2021
DOI: 10.3390/ma14040802
|View full text |Cite
|
Sign up to set email alerts
|

Double Pulse Resistance Spot Welding of Dual Phase Steel: Parametric Study on Microstructure, Failure Mode and Low Dynamic Tensile Shear Properties

Abstract: Resistance spot welding (RSW) of dual phase (DP) steels is a challenging task due to formation of brittle martensitic structure in the fusion zone (FZ), resulting in a low energy capacity of the joint during high-rate loading. In the present study, in situ postweld heat treatment (PWHT) was carried out by employing a double pulse welding scheme with the aim of improving the mechanical performance of DP590 steel resistance spot weld joint. Taguchi method was used to optimize in situ PWHT parameters to obtain ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…Ayrıca, elde edilen sonuçların istatistiksel güvenilirliği incelenir. Bu amaçla öncelikle, Denklem 2'ye göre sinyal/gürültü (S/N) oranının genel değişkenliğini temsil eden SST değeri (toplam kareler toplamı) hesaplanır (Soomro, 2021).…”
Section: Deney Tasarımı (Doe) Ve Anova Analiziunclassified
“…Ayrıca, elde edilen sonuçların istatistiksel güvenilirliği incelenir. Bu amaçla öncelikle, Denklem 2'ye göre sinyal/gürültü (S/N) oranının genel değişkenliğini temsil eden SST değeri (toplam kareler toplamı) hesaplanır (Soomro, 2021).…”
Section: Deney Tasarımı (Doe) Ve Anova Analiziunclassified
“…Kishore et al [ 10 ] compared the processes of welding for steel with and without a zinc coating and found that during the welding process, the coating on the surface of the steel reduces the diameter of the weld nugget. Soomro et al [ 11 ] proposed the use of double pulse resistance spot welding as a postweld heat treatment method that improves the mechanical properties of the spot weld. On the basis of the research, it was found that for galvanized dual phase (DP590) steel, the most important parameter influencing the mechanical performance of the spot weld is the welding current, then the welding time and the cooling time (for double pulse resistance spot welding).…”
Section: Introductionmentioning
confidence: 99%
“…Pulse, elektron ışını malzemelerin mikroyapısıyla faz kompozisyonunu değiştirerek alan niteliklerini ilerletmesini sağlayan kaynaktır [16]. Bu teknoloji, saf tabaka oluşumuna nedendir [17].…”
Section: Gi̇ri̇ş (Introduction)unclassified